Combined antiseptics for external use based on Streptomyces albus products - Wu, Lin; Todosiichuk, T.S. (Problems of Environmental Biotechnology, 2023)
The aim of the presented work was the development of combined antiseptics based on a complex of enzymes (Cytal) and antibiotics (Streptofungin) from S. albus 2435. As a result of the work, an ointment form of a combined antiseptic was developed, which has a wider spectrum of antimicrobial action than comparative drugs and combines the leading bacteriolytic effect of Cytal and the fungicidal action of Streptofungin; has a 10-13% increased ability to inhibit the growth of S. aureus and C. albicans than individual drugs, respectively. The liquid form of the combined antiseptic showed high activity in preventing the formation of biofilms of the test cultures. Therefore, the developed compositions of antiseptics have prospects as means of treating superficial wounds of various etiologies.